PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015-2018 - Rizka Dwi Ayunin Tisna; Nur Diana; Afifudin Afifudin (Universitas Islam Malang, 2020)
ABSTRACTThis research was conducted to determine the effect of green accounting on the profitability of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. In this study the authors took a sample of 54 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. The analytical method used is multiple linear regression. Based on results of tests that have been done, it can be concluded that simultaneously environmental performance variables and environmental costs have a significant effect on the profitability of manufacturing companies. Partial test result indicate that environmental performance variables do not affect the profitability of manufacturing companies. While the environmental cost variable partially has a negative and significant effect on the profitability of manufacturing companies. Keywords : Green accounting, environmental performance, environmental costs and profitability